Tibial Tubercle Avulsion Fracture with Multiple Concomitant Injuries in an Adolescent Male Athlete - Avinesh Agarwalla; Richard Puzzitiello; Austin V. Stone; Brian Forsythe (Case Reports in Orthopedics)
Tibial tubercle avulsion fractures are an uncommon injury occurring due to strong contraction of the quadriceps femoris muscle during leg extension, ultimately causing failure of the physis at the patellar tendon insertion. This injury has been previously reported with various concomitant injuries, such as compartment syndrome from bleeding into the anterior compartment, vascular injury, patellar tendon avulsion, and meniscal injury—exhibited only with fracture types that extend intra-articularly. We report the case of a 14-year-old healthy adolescent male basketball player who sustained this injury as a result of a collision with another player. He initially reported to the emergency department and then presented to our practice, where he was diagnosed with a tibial tubercle avulsion fracture with patellar tendon rupture. During the operative management of these injuries, it was noted that fascial tissue avulsed through the injury site causing subacute extensive bleeding within the anterolateral compartments. Due to concerns of compartment syndrome, a fascial release was performed along the anterolateral compartments. By five months postoperatively, the patient demonstrated near-normal function, no evidence of extensor lag, and nearly full range of motion. Unlike previously reported cases, this is the first report of a patient who suffered such an injury with multiple concomitant injuries to the neighboring structures. Due to the severity of compartment syndrome and the variability in its temporal presentation from the initial injury, it is paramount that careful evaluation of vascular integrity and a low threshold for fasciotomy be in place to prevent vascular compromise.